Conception of digital nuclear power station - Yingrong WANG; Xiuliang XU; Shuyuan CAO (Dianxin kexue)
A new digital nuclear power station architecture blueprint and plan were put forward. With the concept of the full lifecycle management of nuclear power station，design data，construction data，commissioning data，real-time data and business process data for the project were integrating effectively from engineering period to operation period. Adopting advanced information technology，an intelligent or digital nuclear power station would be constructed to achieve resource sharing across platforms for structured data and unstructured data. The concept，significance，progress of digital nuclear power station were introduced，and the idea of construction of digital nuclear power plant information platform was put forward. Data center and information platform were established respectively，so as to realize the real meaning of digital nuclear power station.